تطور مهارات الحاسوب لدى طلبة قسم اللغة العربية في كلية التربية الاساسية / جامعة ديالى - د رياض حسين علي أ .; م فتحي حمدي لطيف النعيمي م . (Journal of College of Education, 2021)
This research aims to measure the development of computer skills among students of the Arabic language department at the basic / Diyala University College of Education for the academic year 2016/2017. The research sample consisted of the initial study students (the four stages) totaling (44) students, and graduate students (master’s and doctoral) totaling (26) students and reached the total sample (70) students. The researchers formulated the following hypotheses: 1. There is no difference is statistically significant at the level (0.50) between the average grades of primary school students (Phase IV) and central premise in the posttest. 2. There is no difference is statistically significant at the level (0.50) between the average scores of graduate students and central premise in the posttest. 3. There is no difference is statistically significant at the level (0.50) between the average grades of primary school students (Phase IV) and postgraduate studies in the posttest. 4. There is no difference is statistically significant at the level (0.50) between the average sample grades (students of the initial study and graduate) and central premise in the posttest. To achieve the aim of the research, the researchers prepared a test of computer skills of multiple choice and be one of the (30) items were confirmed sincerity and persistence (reliability coefficient 83.0) and the researchers used statistical methods: Altaia test (T.test) for one sample, and the test Altaia (T .Test) for two independent samples, Cronbach’s alpha coefficient (Cronbach’s alpha) to measure the stability of search tool. After analyzing the results statistically showed the following results: 1. There is weakness in the level of computer skills among primary school students (fourth stage). 2. There is a development in the level of computer skills among graduate students (Masters and PhD). The researchers recommended a number of recommendations including: • The need for a computer considered essential items in the stages of university education, and the provision of modern techniques in computer teaching. The researchers suggest a number of proposals including: • Conduct studies to find the relationship of computer skills for each of the following variables: (teaching strategies, tendencies, impulses).